Comparison Of Effectiveness in Real-Time Ultrasound Guided Spinal Anaesthesia Versus Pre-Procedural Ultrasound Guided Spinal Anaesthesia in Obese Parturients: A Randomized Clinical Trial - Hiremath, Suman; S. D, Pratibha; Holyachi, Renuka; L. K, Shivanand (Journal of Neonatal Surgery, 2025)
Background: The standard method for elective caesarean sections is spinal anaesthesia, however, in obese parturients, we may find it difficult to use conventional landmark-guided techniques in identifying anatomical landmarks, leading to multiple attempts and increased risk of complications. Neuraxial ultrasound-guided (USG) techniques offer a promising solution by enhancing procedural accuracy and efficiency. Aim: Aim of our study is to evaluate the efficacy of pre-procedural ultrasound-guided (PPUS) and real-time ultrasound-guided (RUS) spinal anaesthesia in obese parturients undergoing elective caesarean sections. Materials and Methods: A total of 80 obese parturients (BMI >30 kg/m2, ASA II-III) scheduled for elective cesarean sections were randomized into two groups: Group RUS and Group PPUS. Primary outcomes includes the number of attempts, needle passes, and time taken for successful dural puncture. Secondary outcomes includes intervertebral space identification time, successful analgesia time and hemodynamic stability. Statistical analysis was performed using SPSS v20 with p< 0.05 considered significant. Results: Attempts and needle passes were significantly less in Group RUS than in Group PPUS. In Group RUS, the average time for both successful lumbar puncture and intervertebral space identification was less. Conclusion: Both RUS and PPUS techniques are effective for spinal anesthesia in obese parturients. However, RUS was significantly better technique in decreasing the number of attempts, needle passes, and procedural time, making it a more efficient and precise approach.